Spatial Resolution of Low-Density OPM-MEG: A Comparative Analysis With High-Density EEG - Gao, Zhenfeng; Cao, Fuzhi; An, Nan; Li, Wen; Wang, Wenli; Yang, Jianzhi; Wang, Dawei; Ning, Xiaolin (IEEE transactions on instrumentation and measurement, 2025)
Electroencephalography (EEG) and magnetoencephalography (MEG) are noninvasive neuroimaging techniques used to detect and localize brain activity. Unlike cumbersome MEG systems that employ superconducting quantum interference devices (SQUIDs), EEG and the emerging optically pumped magnetometer-based MEG (OPM-MEG) systems are wearable and compact, allowing subjects to move naturally during data acquisition. With limited sensor numbers, OPM sensors can be locally arranged for the brain area of interest to enhance the spatial resolution. In this study, we aimed to investigate the spatial resolution of low-density OPM-MEG with locally arranged sensor arrays by comparing it with high-density EEG, providing insights into its practical application. Simulations of three 32-channel local arrays targeting functional brain regions were compared to those obtained via a 128-channel EEG by using the resolution matrix as an indicator. To align with real-world scenarios, we further investigated the mechanism by which skull conductivity and co-registration errors affect source localization accuracy. We conducted median nerve stimulation (MNS) experiments using both the constructed OPM-MEG and EEG to validate their source localization performance. The simulation results demonstrated that OPM-MEG provides spatial specificity comparable to or even exceeding EEG. In real-world experiments, both modalities achieved accurate localizations, with similar source distributions. Simulations and experiments confirmed the comparable spatial localization performance of both systems, highlighting the potential of low-density OPM-MEG for research on a specific brain function. Low-density OPM-MEG presents a promising alternative to high-density EEG, potentially improving accuracy, and participant comfort.